The role of Fetuin-A and Leucine-rich α-2-glycoprotein in the diagnosis of prostate cancer - a pilot study - Sorokac Kubolkova, Alena; Varga, Gabriel; Benovska, Miroslava; Kovacova, Lenka; Fedorko, Michal (Biomedical papers, 2024)
Background. Prostate cancer (PC) is one of the most frequently diagnosed non-skin solid cancers and is a leading cause of cancer-related death and the incidence increasing. Early diagnosis of the disease improves the outcomes. There is an urgent need for new biomarkers with greater discriminative precision for diagnosis, risk-stratification and treatment. The aim of our study was to evaluate the diagnostic and prognostic potential of Fetuin-A and LRG1 in patients with PC.Methods. Serum levels of Fetuin-A and LRG1 were compared in patients with PC (n=46), a control group 1 including young, healthy subjects (n=26) and control group 2 including patients with negative prostate biopsy (n=46). In PC patients, the levels of both biomarkers were compared in subgroups with different tumour characteristics.Results. We demonstrated a statistically significant higher concentrations of Fetuin-A in PC patients compared to control group 2 (439 mg/L vs. 372 mg/L), P<0.001. No statistically significant difference was found between PC patients and control group 1, nor for LRG1 levels between the three groups. In PC patients, higher serum levels of LRG1 were found in M1 patients compared to M0 (98 mg/L vs. 42 mg/L), P=0.059.Conclusion. Fetuin-A levels are significantly higher in patients with prostate cancer than in patients without malignancy but LRG1 levels do not differ between patients with PC and controls.
Keywords: biomarker; Fetuin-A; LRG1; prostate cancer; serum